SYSTEM OF DEVELOPMENT OF SOCIAL PEDAGOGICAL COMPETENCE OF FUTURE TEACHERS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
In this article, it is shown to theoretically justify the development of pedagogical competence qualities in future teachers and to develop methodologicalrecommendations for the creation of teacher pedagogical competence qualities in the process of training qualified personnel